Identificação e estudo do fungo Mucor circinelloides isolado do tronco de Pinus taeda, com ênfase em biotransformação da carvona - Santos, Gabriel Franco dos (2012)
Identification and study of the fungus Mucor circinelloides isolated from the trunk of Pinus taeda, with emphasis on the carvone biotransformation. Fungi associated with plants have been studied ripping seeking the discovery of new substances and the understanding of the ecological interactions between plants and microorganisms. This study aimed to identify a fungus associated with the trunk of Pinus taeda using morphological analysis with images obtained by optical microscopy and scanning electron microscopy (SEM), genetic sequencing of the 18S ribosomal region, and proteome analysis by MALDI-TOF. The fungus was identified as Mucor circinelloides and its metabolism was studied. A mixture of 3-epiergosterol and ergosterol, glucosilceramidas mixture, and 3-glucopyranosyl-sitosterol were identified. The emphasis of this work was on the biotransformation of carvone, which is one of the main monoterpenes found in nature and one of the most commercialized. From the biotransformation experiment it was possible to isolate two trihydroxylated products and also dihydrocarvona, dihydrocarveol and neo-dihydrocarveol identified by GC-MS. The biotransformation products were identified by GC-MS and were proposed a pathway biotransformation. After that was performed also an estimative of production for some products and consumption estimated of (4R) - and (4S)-carvone, which is consumed in less than four hours of the experiment, showing a very rapid metabolism as reported in several genera of Mucor.